Arginine-rich histones have strong antiviral activity for influenza A viruses. Issue 7 (October 2015) - Hoeksema, Marloes; Tripathi, Shweta; White, Mitchell; Qi, Li; Taubenberger, Jeffery; van Eijk, Martin; Haagsman, Henk; Hartshorn, Kevan L
While histones are best known for DNA binding and transcription-regulating properties, they also have antimicrobial activity against a broad range of potentially pathogenic organisms. Histones are abundant in neutrophil extracellular traps, where they play an important role in NET-mediated antimicrobial killing. Here, we show anti-influenza activity of histones against both seasonal H3N2 and H1N1, but not pandemic H1N1. The arginine rich histones, H3 and H4, had greater neutralizing and viral aggregating activity than the lysine rich histones, H2A and H2B. Of all core histones, histone H4 is most potent in neutralizing IAV, and incubation with IAV with histone H4 results in a decrease in uptake and viral replication by epithelial cells when measured by qRT-PCR. The antiviral activity of histone H4 is mediated principally by direct effects on viral particles. Histone H4 binds to IAV as assessed by ELISA and co-sedimentation of H4 with IAV. H4 also induces aggregation, as assessed by confocal microscopy and light transmission assays. Despite strong antiviral activity against the seasonal IAV strains, H4 was inactive against pandemic H1N1. These findings indicate a possible role for histones in the innate immune response against IAV.